The Medicine Boxes on Compliance with Taking Anti-Tuberculosis Medication in Tuberculosis Patients: Case Study - Setiyowati, Eppy; Marliana, Lya; Dewi, Arie Kusumo; Listari, Risti Puji (Chakra Brahmanda Lentera Institute, 2023)
Background: Tuberculosis (TB) is a chronic, infectious disease that is still a health problem in society, including Indonesia. India is still the second country contributing to the highest incidence of TB in the world after India. The aim research was to present an analysis of the successes and challenges in implementing the medicine box implementation strategy to increase TB patient compliance with ANTI-TUBERCULOSIS MEDICATION treatment. Methods: The method used is descriptive with a case study approach through parenting with the problem of maintaining medication non-adherence in Tuberculosis patients. Data was collected using interview methods, direct observation, and medical records. Results: The results of using the medicine box for three days on Mr It was found that there was a gradual increase in compliance with taking medication after using it. Applying this medicine box is practical in increasing compliance with taking medication experienced by Tuberculosis patients Conclusion: Therefore, nurses are expected to be able to teach how to use the medicine box according to standard operating procedures (SOP) so that patients and their families can practice again at home